The Role of Composites for Sustainable Society and Industry - Ragil Widyorini; Nasmi Herlina Sari; Muji Setiyo; Gunawan Refiadi (Universitas Muhammadiyah Magelang, 2021)
In the last few decades, the global community's demands are getting stronger for more environmentally friendly materials. Natural fiber reinforced composites have been applied as reinforcement in concrete, sound absorbers, buildings, aeronautical, aerospace, sanitation, electronics, bridge decks, interior, automotive, sports equipment and furniture industries, modular structures, and others. Natural fibers are receiving high attention due to their sustainability, environmental friendliness, low density, low cost, low abrasiveness, renewability, and biodegradability, as well as contributing to the consumption of CO2 gas. As reported by many researchers, Indonesia has several natural resources for natural fibers such as bark fiber, leaf fiber, seed/fruit fiber, grass fiber, stalk fiber, and wood fiber.